Salidroside, A Natural Antioxidant, Improves β-Cell Survival and Function via Activating AMPK Pathway - Linjie Ju; Linjie Ju; Xiaohua Wen; Xiaohua Wen; Chunjun Wang; Chunjun Wang; Yingjie Wei; Yingjie Wei; Yunru Peng; Yongfang Ding; Liang Feng; Liang Feng; et al. (Frontiers Media S.A., 2017)
Aim: The enhanced oxidative stress contributes to progression of type 2 diabetes mellitus (T2DM) and induces β-cell failure. Salidroside is a natural antioxidant extracted from medicinal food plant Rhodiola rosea. This study was aimed to evaluate protective effects of salidroside on β-cells against diabetes associated oxidative stress.Methods and Results: In diabetic db/db and high-fat diet-induced mice, we found salidroside ameliorated hyperglycemia and relieved oxidative stress. More importantly, salidroside increased β-cell mass and β-cell replication of diabetic mice. Mechanism study in Min6 cells revealed that, under diabetic stimuli, salidroside suppressed reactive oxygen species production and restore mitochondrial membrane potential (ΔΨm) via reducing NOX2 expression and inhibiting JNK-caspase 3 apoptotic cascade subsequently to protect β-cell survival. Simultaneously, diabetes associated oxidative stress also activated FOXO1 and triggered nuclear exclusion of PDX1 which resulted in β-cell dysfunction. This deleterious result was reversed by salidroside by activating AMPK-AKT to inhibit FOXO1 and recover PDX1 nuclear localization. The efficacy of salidroside in improving β-cell survival and function was further confirmed in isolated cultured mouse islets. Moreover, the protective effects of salidroside on β-cells against diabetic stimuli can be abolished by an AMPK inhibitor compound C, which indicated functions of salidroside on β-cells were AMPK activation dependent.Conclusion: These results confirmed beneficial metabolic effects of salidroside and identified a novel role for salidroside in preventing β-cell failure via AMPK activation. Our finding highlights the potential value of Rhodiola rosea as a dietary supplement for diabetes control.